Cardiac arrhythmia in refrigerator repairmen exposed to fluorocarbons. Issue 3 (March 1990) - Edling, C; Ohlson, C G; Ljungkvist, G; Oliv, A; Söderholm, B
Abstract : A field study of 89 refrigerator repairmen was carried out to ascertain whether occupational exposure to fluorocarbons induces cardiac arrhythmia. The concentrations of fluorocarbons in the breathing zones and the heart activity were recorded simultaneously. Most cooling systems contained FC 12 or FC 22. The highest level recorded in one minute was 14, 000 ppm and the highest time weighted level during eight hours was 280 ppm. Two types of arrhythmia were recorded, ectopic beats and sudden bradycardia. A within subject comparison design was applied and the main parameter was the difference in arrhythmia frequencies between exposed and unexposed periods. No appreciable differences between exposed and unexposed periods and no consistent dose effect relations were observed, although subjects in the medium exposure category showed a difference of borderline significance (Wilcoxon's test: p = 0.05, one tailed). The frequencies of arrhythmia when unexposed were somewhat higher than previously reported. Misclassification of the exposure and the possible confounding effect of physical workload and psychological strain may have obscured a causal relation and therefore a minor effect cannot be ruled out. The results do not support the notion that fluorocarbons induce cardiac arrhythmia in occupationally exposed refrigerator repairmen.